2020
DOI: 10.21203/rs.2.20636/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of hsa_circ_0005243 induces trophoblast cell dysfunction and inflammation via the β-catenin and NF-κB pathways

Abstract: Background: Gestational diabetes mellitus (GDM) is a common complication in pregnancy that poses a serious threat to the health of both mother and child. While the specific etiology and pathogenesis of this disease are not fully understood, it is thought to arise due to a combination of insulin resistance, inflammation, and genetic factors. Circular RNAs (circRNAs) are a special kind of non-coding RNA that have attracted significant attention in recent years due to their diverse activities, including a potenti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Notably, the NF‐κB signaling pathway was enriched (Figure 6B), and the DEGs were involved in cell adhesion, cell death, extracellular matrix organization and EMT, as indicated by GO analysis (Figure 6C). It has been reported that ankyrin repeat proteins can regulate the NF‐κB pathway, 21 and that the ANKRD protein family can regulate NF‐κB signaling pathway, 15,22,23 and also that the NF‐κB signaling pathway is involved in regulating EVT functions 24 . Therefore, we further explored the effects of ANKRD37 on NF‐κB signaling using Western blotting to detect the IκBα and p65 phosphorylation levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the NF‐κB signaling pathway was enriched (Figure 6B), and the DEGs were involved in cell adhesion, cell death, extracellular matrix organization and EMT, as indicated by GO analysis (Figure 6C). It has been reported that ankyrin repeat proteins can regulate the NF‐κB pathway, 21 and that the ANKRD protein family can regulate NF‐κB signaling pathway, 15,22,23 and also that the NF‐κB signaling pathway is involved in regulating EVT functions 24 . Therefore, we further explored the effects of ANKRD37 on NF‐κB signaling using Western blotting to detect the IκBα and p65 phosphorylation levels.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ankyrin repeat proteins can regulate the NF-κB pathway, 21 and that the ANKRD protein family can regulate NF-κB signaling pathway, 15,22,23 and also that the NF-κB signaling pathway is involved in regulating EVT functions. 24 Therefore, we further explored the effects of ANKRD37 on NF-κB signaling using Western blotting to detect the IκBα and p65 phosphorylation levels.…”
Section: Ankrd37 Inhibited the Nf-κb Pathway In Trophoblast Cellsmentioning
confidence: 99%
“…Accumulating circRNAs have been reported to have potential regulatory roles in GDM [22]. For instance, a previous study demonstrated that the knockdown of circ_0005243 suppresses the proliferation and migration of trophoblast cells [23]. Circ_0008285 is related to increased glycated hemoglobin, and its knockdown alleviates the progression of GDM [24].…”
Section: Discussionmentioning
confidence: 99%
“…GDM is a common complicated impregnate threat [21, 22]. Most GDM is found for the first time during pregnancy [23].…”
Section: Discussionmentioning
confidence: 99%